The role of the interior design in selected breastfeeding stations in providing comfort and efficiency as perceived and experienced by a breastfeeding mother - Gutierrez, Ma. Pamela S.
ABSTRACT This case study sought to determine the role of interior design in selected breastfeeding stations of Ayala Malls in providing comfort and efficiency as perceived and experienced by a breastfeeding mother. The study involved three breastfeeding stations that were chosen through convenience sampling and were assessed in terms of lighting, color scheme, furniture, and other interior elements based on the requirements of the Expanded Breastfeeding Promotion Act of 2009 (R.A. 10028). The sole respondent of the study was chosen through purposive sampling, for which she has to be a currently breastfeeding mother. The data of this study were obtained through observations, non-directive interviews, and key informant interviews. The data was then categorized according to the different methods of data gathering and analyzed by correlating the results with the Theory of Supportive Design. The results and analysis showed that among the categories assessed, furniture had the greatest impact on the respondent's perceptions on comfort and efficiency. The seating in particular affected the respondent the most since it provided interaction with the respondent through direct physical content. It was also analyzed that among all the breastfeeding stations included in the study, only Station 1 was able comply with all the requirements of R.A. 10028. This study may provide insights for future interior designers to consider the needs and preferences of breastfeeding mothers when designing breastfeeding stations. Furthermore, this study recommends increasing the number of respondents and breastfeeding stations to be assessed in order to provide more general outcomes and applications.